Capability of an ultrasonic system to detect very early caries lesions on human enamel - Bozkurt, Funda Öztürk; Tağtekin, Dilek; Yanıkoğlu, Funda; Fontana, Margherita; Gonzalez-Cabezas, Carlos; Stookey, George K. (Marmara Dental Journal, 2013)
The purpose of this investigation was to determine if changes in dental enamel with 20 micron depth incipient carious lesion could be detected by an ultrasonic system (US). Natural (unground, unpolished) lesions were produced on human enamel by using a microbial caries model. Specimens with lesions were analyzed using Ultrasonic system (US) as test method, Quantitative-Light Induced Fluorescence (QLF) and Confocal Laser Scanning Microscopy (CLSM) as gold standards. It was found that both ultrasound and QLF could not detect these very early lesions (mean lesion depth: 18.89 μm) created in vitro in the microbial caries model.
Keywords: Ultrasound, Microhardness, QLF, Confocal Microscope, PreWhite Spot Caries Lesion